RISK OF OVERWEIGHT AMONG TEENAGERS WHO FOND TO CONSUME FRIED FOOD IN LOH SUMBER, KUTAI KARTANEGARA - Niken Agus Tianingrum; Aliyansyah Mustofa; Ayunda Dianandari; Mira Susanti; Sarmawati Sarmawati (Jurnal Ilmu Kesehatan, 2020)
Teenager (12-18 years old) was a period that is vulnerable to nutritional problem. This is due to two reasons, because the teenager needs more nutrition for physical growth and for psychological development. It is also susceptible to changes in lifestyle and eating patterns. The purpose of this research was to know the risk of overweight among teenagers who fond to consume fried food in Loh Sumber, Kutai Kartanegara. This research was a quantitative with cross sectional design to 80 respondents. The sampling technique used a rapid survey method ang questionnaire as research instrument.. Data was analyzed by chi square test. The result of the research showed the overweight teenagers were as many as 26 people (32,5%) and the result of statistical analysis showed that fried foods has a significant association (P-value=0,004; OR=12,5; CI=0,233 – 3,616). The teenagers who fond to consume fried food have a 12,5 times greater risk of getting overweight compared with those who did not fond consume fried food. Therefore, it is recommended to teenager to improve the eating pattern and increase the physical activity.